Micro Business Development Strategy To Optimize Business Locations Culinary Tourism Area - Mawuntu, Priska Shirty Thelma; Aotama, Reynaldo Christian (Jurnal Entrepreneur dan Entrepreneurship, 2019)
This study aims to identify and analyze the factors that influence the appropriate alternative strategies, and priority strategies for the development of micro businesses in the culinary tourism area. This research uses descriptive qualitative method by collecting data through interviews. Data were analyzed using three stages of strategy formulation: input stage, matching stage, and decision stage. This study found that the factors that influence the development of micro businesses in culinary tourism areas are varied products, low managerial ability of business owners, technological and information development, and changes in lifestyle and people’s interest in culinary products. Second, appropriate alternative strategies are to increase production capacity, maintain affordable product prices, provide adequate supporting facilities, take management training for business owners, conduct simple financial records, increase marketing through digital marketing, collaborate with suppliers of raw materials, and improve product quality and innovation. Third, a priority strategy in developing micro businesses in the culinary tourism area is to improve product quality and innovation.